Lexico-Grammatical Features of a Managing Guidelines Document Based on Biber’s Multidimensional Analysis - Santos, Valeria Branco Moreira Pinto dos (The ESPecialist, 2012)
This article presents and discusses the results of a Multidimensional Analysis (MDA) (Biber, 1988 & 1995) adapted to a written business corpus in Portuguese. A document called ‘Manual de Gestão’ (“Managing Guidelines”), collected in a Brazilian company, was submitted to the program WordSmith Tools (Scott, 1999) for key-word survey. The resulting key-word list was analysed according to grammatical traces, and then, contrasted to the Multidimensional clines. Results show that this document fits both the positive (+) and the negative (-) poles in different dimensions, either matching Biber’s findings, or revealing new possibilities of framing. These outcomes suggest that ‘Manual de Gestão’ belongs to a special category of genre because it shares discourse features with other genres. In addition, the study also brought up issues on the application of MDA to the Portuguese language, which will be discussed throughout the article.